Family Support in Accompanying Post-Stroke Patients Undergoing Physiotherapy: Assessed from the Onset of the Stroke - Sinaga, Mei Rianita Elfrida; Purnomo, Veronika Debi (Jurnal Ilmiah Kesehatan, 2025)
Stroke is a disease with a prevalence of 10.9% in 2018, which increased by 3,9% over the last five years, leading to complications such as weakness of physical limbs. Family support influences post-stroke patients' recovery through emotional, appreciation, instrumental, and information support. This study describes family support in accompanying post-stroke patients undergoing physiotherapy after 1-6 months of the stroke attack. The results showed that most respondents were aged 56-65 years (43.1%), male (52.9%), and retired/not working (31.4%). In addition, they had a senior high school education (39.2%), and the type of stroke was ischemic stroke or non-hemorrhagic stroke (62.8%). Family support in accompanying post-stroke patients undergoing physiotherapy after 1-6 months of the attack was mainly in the good category, namely 48 respondents (94.1%). The most significant type of family support was emotional support, as shown by the choice "always" in item 2, with 50 respondents. In conclusion, family support in accompanying post-stroke patients undergoing physiotherapy after 1-6 months of the stroke attack is good, especially in emotional support. Thus, families should maintain and increase family support so that post-stroke patients have the motivation to undergo routine checkups and physiotherapy.